VD_FINDINFO HC / 2010 / 232 vom 23. April 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, DROIT D'ÊTRE ENTENDU, INTERDICTION DE L'ARBITRAIRE | 29 al. 2 Cst., 13 al. 2 LPEBL, 13 LPEBL, 23 al. 2 LPEBL, 23 LPEBL